CASE REPORT BLEPHAROCONJUNCTIVITIS AS MANIFESTATION OF STEVENSJOHNSON SYNDROME - Saraswati Surya, Putu Ayu Adindhya; Sunariasih, Ni Nyoman (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Background: Stevens Johnson syndrome (SJS) is a collection of acute and life threatening skin symptoms caused by an allergic drug reaction. SJS also attacks the other mucous membranes, one of which is the eye. SJS is a rare case. The initial complaint of SJS is the eruption on the skin in the form of redness followed by blisters and attacking other mucous membranes. The ocular manifestations of SJS are conjunctivitis, corneal erosion, corneal ulcers, and blepharitis. Methods: Treatment of SJS’s ocular manifestation is administration of drugs and surgical intervention. Administration of drugs that often done in the acute phase is antibiotic eye drops with steroids to prevent complications. Complications that can occur include symblepharon, districhiasis, and keratitis. This complication can cause a sharp decrease in vision. Results: This case report discusses a 68 year old male patient with blisters all over his body accompanied by swelling in both eyes, redness in both eyes, and difficult to open eyes. Patients with history of taking the new drug a month ago. No history of drug allergy. The patient suffered from hypertension, non-hemorrhagic stroke, and epilepsy with irregular treatment. Patient was performed a fluorescein test. In this case, the patient is given antibiotic ointment and artificial tears with steroids. In this case there were no complications. Conclusion: The ocular manifestations of SJS if handled quickly and properly can prevent long-term complications.